Anti-malarial seroprevalence assessment during an elimination programme in Chabahar District, south-eastern Iran. (December 2016) - Zakeri, Sedigheh; van den Hoogen, Lotus; Mehrizi, Akram; Karimi, Fatemh; Raeisi, Ahmad; Drakeley, Chris
Abstract Background Iran has achieved a substantial decline in malaria incidence over the past decades. A common feature of malaria-endemic settings is the requirement for more sensitive techniques to describe levels of low transmission. In this study, serological and parasitological methods were used to measure transmission levels ofPlasmodium falciparum andPlasmodium vivax during an elimination programme (2012) in Chabahar District, Sistan and Baluchistan Province, south-eastern Iran. Methods Participants were randomly selected from 64 different geographical clusters in Chabahar city and surrounding villages. Antibody responses toP. falciparum andP. vivax blood-stage antigens were assessed by ELISA, while microscopy and molecular testing were used to determine parasite carriage by species. Age-adjusted antibody responses were analysed using a reversible catalytic model to calculate seroconversion rates (SCR). Results There was no evidence of recent transmission in the study areas, indicated by an absence of parasite infections in all ages and low or absent serological responses to either species in young children. The best model for ageP. falciparum seroconversion was one with a change in exposure 21 years before sampling was done in Chabahar city (P  = 0.018) and 4 years in the villages (P  = 0.039). There was a higher level of recentP. vivax transmission compared toP. falciparum, based on the SCRs, in both the city and village settings. Conclusion Serological analysis identified a decline inP. falciparum transmission in the urban areas of Chabahar, consistent with a previously described decrease in malaria in the early 1990s, demonstrating the utility of this approach to reconstruct exposure history. At present, it remains unclear whether theP. vivax antibody responses reflect active transmission due to new infections or relapse infections. The absence of parasitological and serological evidence of recent malaria transmission in Chabahar District is viable evidence for certification of elimination.